Anatomical templates of lymph node dissection for upper tract urothelial carcinoma: a systematic review of the literature. Issue 3 (4th March 2017) - Campi, Riccardo; Minervini, Andrea; Mari, Andrea; Hatzichristodoulou, Georgios; Sessa, Francesco; Lapini, Albero; Sessa, Maurizio; Gschwend, Jurgen Erich; Serni, Sergio; Roscigno, Marco; Carini, Marco
ABSTRACT: Introduction: Indications and techniques of lymph node dissection (LND) for upper tract urothelial carcinoma (UTUC) are still controversial. Areas covered: In this study, a systematic review of the English-language literature was performed up to 1 July 2016 using the Medline, Scopus, Cochrane Library and Web of Sciences databases to provide a detailed overview of the most commonly dissected surgical templates of LND for UTUC according to laterality and location of the tumor. Overall, sixteen studies were analyzed. Based on the shared experiences in the scientific literature, the LND template typically included: for right-sided tumors of the renal pelvis, upper third and middle third of the ureter, the renal hilar, paracaval, precaval and retrocaval nodes, while for l eft-sided tumors the renal hilar, paraaortic and preaortic nodes. For tumors of the lower ureter, an extended pelvic LND was performed in most cases; however, the paracaval, paraaortic or presacral nodes were dissected in selected series. Expert commentary: LND is not routinely performed at the time of surgery for UTUC and both indication and extent of LND vary among surgeons and institutions. Future high-quality studies are needed to define the most accurate LND templates and to assess their oncological efficacy and surgical morbidity.